Optimization of oil yield of Phaleria macrocarpa seed using response surface methodology and its fatty acids constituents - Azmir, J.; Sarker, Md. Zaidul Islam; Rahman, Md. Mokhlesur; Sharif, K.M.; Ferdosh, Sahena; Jahurul, M.H.A.; Mohamed, A. (Elsevier, 2014)
Phaleria macrocarpa (Mahkota dewa) seed was examined to determine the optimal conditions of oil yield by solvent extraction method using n-hexane as extracting solvent. Response surface methodology (RSM) was employed to describe explicitly the influence of extraction time, temperature and solvent-to-feed ratio on the yield of oil using central composite design (CCD). The linear, quadratic and interaction terms of the studied variables have significant (P < 0.05) effect on the oil yield. The temperature of 72 °C, extraction time of 8.4 h and solvent-to-feed ratio of 10.9 ml/g were the optimal conditions for seed oil extraction. The maximum oil yield was 55.32 g/100 g dry weight under these optimal conditions. Main chemical constituents of oil were determined by Gas chromatography–mass spectroscopy (GC–MS) and Fourier transform infrared spectroscopy (FTIR). Twelve components were identified by GC–MS analysis after formation of fatty acid methyl ester (FAME). Total saturated fatty acids were 19.38% whereas monounsaturated fatty acids and polyunsaturated fatty acids were 44.23% and 36.38%, respectively. Oleic acid, 18:1 (43.56%) and linoleic acid, 18:2 (36.25%) were the main fatty acid constituents of Mahkota dewa seed oil. The quantity of unsaturated fatty acids was higher than saturated fatty acids in P. macrocarpa seed oil.